LINGUOCULTUROLOGY AS A BRANCH OF LINGUISTICS - Ibodullaeva Shirina Mirzhakhon qizi (Web of Journals Publishing, 2023)
This article explores the emerging field of Linguoculturology, a distinctive branch of linguistics that investigates the intricate interplay between language and culture. Linguoculturology delves into the ways in which linguistic elements, such as syntax, semantics, and discourse, intersect with cultural phenomena, shaping and reflecting societal norms, values, and identities. Through a multidisciplinary approach, this study aims to unravel the profound connections between language and culture, shedding light on the nuanced dynamics thatinfluence communication within diverse linguistic communities.
Keywords: Linguoculturology; Linguistics; Culture; Language and Society; Intercultural Communication.